Make deep learning algorithms in computational pathology more reproducible and reusable - Wagner, Sophia J.; Matek, Christian; Shetab Boushehri, Sayedali; Boxberg, Melanie; Lamm, Lorenz; Sadafi, Ario; Waibel, Dominik J. E.; Marr, Carsten; Peng, Tingying (Nature medicine, 2022)
Greater emphasis on reproducibility and reusability will advance computational pathology quickly and sustainably, ultimately optimizing clinical workflows and benefiting patient health.